On the Correct Solvability of the Boundary-Value Problem for One Class Operator-Differential Equations of the Fourth Order with Complex Characteristics. (27th September 2009) - Aliev, Araz R.; Gasymov, Aydin A.
Abstract : Sufficient coefficient conditions for the correct and unique solvability of the boundary-value problem for one class of operator-differential equations of the fourth order with complex characteristics, which cover the equations arising in solving the problems of stability of plastic plates, are obtained in this paper. Exact values of the norms of operators of intermediate derivatives, which are involved in the perturbed part of the operator-differential equation under investigation, are found along with these in subspacesW 2 4 ( R + ; H ) in relation to the norms of the operator generated by the main part of this equation. It is noted that this problem has its own mathematical interest.